2015
DOI: 10.1080/10407782.2014.955348
|View full text |Cite
|
Sign up to set email alerts
|

Mean Flow and Thermal Characteristics of a Turbulent Dual Jet Consisting of a Plane Wall Jet and a Parallel Offset Jet

Abstract: The standard high-Reynolds number two-equation k À e model is used to study the flow and thermal characteristics of a dual jet consisting of a plain wall turbulent jet and a parallel turbulent offset jet (hereafter, dual jet). The flow and thermal characteristics are presented in the form of streamlines, mean velocity vector, turbulent kinetic energy, dissipation of turbulent energy, Reynolds stresses, and isothermal contour plots. The variation in local heat flux and local Nusselt number on the bottom wall is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…The decay of normalized maximum velocity (Umax) in the streamwise direction is shown in Figure 4(b) for various amplitudes (0.1,0.3,0.5 and 0.7) of the sinusoidal wavy wall surface. The present results of wavy surface are also compared with the numerical results of Kumar, 41 Vishnuvardhanarao and Das, 42 Pramanik and Das 2 and Bannyassady and Piomelli 43 and experimental results of Lai and Lu 44 and Eriksson et al. 37 of plane wall surface.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The decay of normalized maximum velocity (Umax) in the streamwise direction is shown in Figure 4(b) for various amplitudes (0.1,0.3,0.5 and 0.7) of the sinusoidal wavy wall surface. The present results of wavy surface are also compared with the numerical results of Kumar, 41 Vishnuvardhanarao and Das, 42 Pramanik and Das 2 and Bannyassady and Piomelli 43 and experimental results of Lai and Lu 44 and Eriksson et al. 37 of plane wall surface.…”
Section: Resultsmentioning
confidence: 64%
“…The decay of normalized maximum velocity ðU max Þ in the streamwise direction is shown in Figure 4(b) for various amplitudes (0:1, 0:3, 0:5 and 0.7) of the sinusoidal wavy wall surface. The present results of wavy surface are also compared with the numerical results of Kumar, 41 Vishnuvardhanarao and Das, 42 Pramanik and Das 2 and Bannyassady and Piomelli 43 and experimental results of Lai and Lu 44 and Eriksson et al 37 of plane wall surface. The maximum velocity ðU max Þ of Vishnuvardhanarao and Das 42 and Pramanik and Das 2 remains almost constant till the potential core is consumed; the potential core is consumed near the axial location of X ¼ 10 and X ¼ 6 respectively.…”
Section: Variation Of U Max Along Xmentioning
confidence: 65%
See 1 more Smart Citation
“…Even though similarity solution is achieved for all the cases, the trend is entirely different than the case of a plane wall. 40,41,45 The similarity solution at the crest is different than at the trough. Moreover, the similarity solution is even different for the case of A = 0.7 (see Figure 15(e) and (f)).…”
Section: Resultsmentioning
confidence: 92%
“…The minimum value of ɛn is noticed in the recirculation region and it decreases continuously along the flow direction. Kumar 41 calculated the maximum value of dissipation rate (ɛmax) of an offset jet ( OR = 7.0) for the plane wall as 0.039, while Pramanik and Das 43 noticed the maximum value of ɛ max of offset jet ( OR = 6.5) for inclined plane wall as 0.065. When the wavy surface is used, it is found that the value of ɛ max is located above the nozzle and it decreases as the amplitude of the wavy surface increases.…”
Section: Resultsmentioning
confidence: 99%